Peran Ombudsman Republik Indonesia Dalam Mencegah Potensi Maladministrasi Pada Pelayanan Jaminan Sosial Ketenagakerjaan Bagi Pekerja Informal - Fajar Reza Rivaldi; Muhammad Khoirul Anwar; Nafi Alrasyid (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the role of the Indonesian Ombudsman in preventing potential maladministration in Social Security (Jamsosnaker) services for informal workers. This study uses a descriptive qualitative approach with a literature study as the primary method, reviewing journals, books, regulations, and official documents, including the 2024 Indonesian Ombudsman Systematic Review Report on potential maladministration in Social Security services for informal workers. Data were analyzed descriptively and analytically by grouping, interpreting, and linking findings to the research focus on preventing maladministration. The analysis results illustrate the contribution of the Indonesian Ombudsman in the external supervision of public services and social protection for informal workers in a systematic and comprehensive manner. The results show that the Indonesian Ombudsman proactively carries out its function of preventing maladministration through systemic studies, regulatory advocacy, monitoring, and public education. This strategy is aligned with public service theory and the principles of good governance, increasing transparency, accountability, and fairness in public services. The systemic approach has successfully encouraged governance reform and social protection for informal workers, including farmers and fishermen. However, prevention effectiveness remains limited by a lack of regional regulations, opaque registration practices, weak internal oversight, and limited resources and public understanding. Therefore, adaptive strategies, increased institutional capacity, and enhanced public literacy are needed to ensure optimal maladministration prevention.